2020
DOI: 10.1002/mma.6848
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of shock waves in a non‐ideal gas under the action of magnetic field

Abstract: In this paper, we use power series method to study the propagation of cylindrical shock waves produced on account of a strong explosion in a non-ideal gas under the influence of azimuthal magnetic field. Here, the density is assumed to be uniform and magnetic pressure is assumed to vary according to power law with distance from the symmetry axis in the undisturbed medium. Using power series method, we obtain approximate analytic solutions in the form of a power series in (a 0 /V) 2 , where a 0 and V are the ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Because of several advantages, many non‐linear problems have been solved using the power series method recently. For the latest research work based on the power series method, one may follow the literature available in other works 34–41 . In their study, 34 Siddiqui et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of several advantages, many non‐linear problems have been solved using the power series method recently. For the latest research work based on the power series method, one may follow the literature available in other works 34–41 . In their study, 34 Siddiqui et al.…”
Section: Introductionmentioning
confidence: 99%
“…For the latest research work based on the power series method, one may follow the literature available in other works. [34][35][36][37][38][39][40][41] In their study, 34 Siddiqui et al analyzed the propagation of magnetogasdynamic shock waves and found the first-order approximate analytic solutions. Singh and Arora 35 extended the work presented in Siddiqui et al 34 by considering the gas to be non-ideal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They obtained both analytical and numerical solutions in their work. Singh and Arora [15] used the power series method to investigate the problem of cylindrical shock wave propagation in non-ideal magnetogasdynamics. By expanding the flow parameters in powers of time, a problem of converging cylindrical shock waves in a non-ideal gas with the effect of azimuthal magnetic field has been solved by Singh and Arora [16].…”
Section: Introductionmentioning
confidence: 99%
“…Nath and Singh [18] have studied the cylindrical ionizing shock waves in a self-gravitating gas with a magnetic field. The propagation of strong shock waves in a non-ideal gas under the effect of magnetic field is studied by Singh and Arora [19]. Nath [20] obtained the approximate analytical solution for the blast waves in a self-gravitating perfect gas.…”
Section: Introductionmentioning
confidence: 99%